(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article covers the daily life of the residents of Andijan, Fergana and Namangan regions of the Republic of Uzbekistan in the 1960s-1980s and the state of medical services. Also, the works performed on the health of the population and their provision are also included in this article.